2003
DOI: 10.1034/j.1600-0838.2003.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic behavior and structural properties of the coracoclavicular ligaments

Abstract: During contact sports such as football, hockey or rugby, the coracoclavicular ligaments are commonly ruptured. Currently, the limited biomechanical data on the properties and function of these ligaments have led to debate on the "gold standard" treatment for these injuries. Therefore, the objective of this study was to characterize the geometry, viscoelastic behavior and structural properties of the coracoclavicular ligaments (n=11). The trapezoid and conoid were found to have similar length (9.6+/-4.4 vs. 11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 26 publications
3
30
0
1
Order By: Relevance
“…The trapezoid ligament expanded to 2.15 cm at the clavicular level, a similar feature that we found at the level of MCCL attachment to coracoid process. The CCL geometry in another study gave somewhat smaller dimensions and, interestingly, no significant differences could be demonstrated between conoid and trapezoid ligament [4]. On the other hand, Ockert et al found the ligaments to be larger than in the previous two studies, precisely distinguishing the 3D components-length, width, and depth [15].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The trapezoid ligament expanded to 2.15 cm at the clavicular level, a similar feature that we found at the level of MCCL attachment to coracoid process. The CCL geometry in another study gave somewhat smaller dimensions and, interestingly, no significant differences could be demonstrated between conoid and trapezoid ligament [4]. On the other hand, Ockert et al found the ligaments to be larger than in the previous two studies, precisely distinguishing the 3D components-length, width, and depth [15].…”
Section: Discussionmentioning
confidence: 82%
“…In the report of Satler et al [17] the histological sections included the plenitude of the acromioclavicular joint with the surrounding ligaments, in order to study better the anatomical relationships of the structures in question. Based on tensile testing and not on histology, no statistically significant differences could be demonstrated for all structural properties between the conoid and trapezoid ligament [4]. A comprehensive immunochemistry study, carried out on CCL complex, revealed fibrocartilage at the level of both clavicular and coracoid entheses, considering it a consequence of adaptation to compression and shear forces [15].…”
Section: Discussionmentioning
confidence: 99%
“…We have not addressed parameters such as failure under anterior and posterior loading and rotational motion. However, the stability in the frontal plane has been evaluated to be the limiting capacity of a coracoclavicular augmentation, while the coracoclavicular ligaments serve as the main stabilizer in the superio-inferior direction [5][6][7]. The parameters studied were chosen because they seem to be most relevant to the clinical process.…”
Section: Discussionmentioning
confidence: 99%
“…The distance between the inferior cortex of the clavicle bone and the superior cortex of the coracoid bone was standardized: 10 mm in the superio-inferior direction and 6 mm in the anterio-posterior direction, resulting in spatial distance of 12 mm. These distances as well fit the physiologic dimensions [5,12,26]. All bones were stored at -20°C temperature.…”
Section: Coracoclavicular Bone Modelmentioning
confidence: 99%
“…2,[4][5][6][7][11][12][13][14]17,23 However, these anatomic and biomechanical studies were typically performed on an isolated structure and do not provide insight into the complex interplay between the AC joint capsule and CC ligaments. In addition, there are no direct comparisons of the biomechanical characteristics or relative contribution of these structures to AC joint stability.…”
mentioning
confidence: 99%